We find the general solution of the equation
"\\frac{dy}{dx} +(cotx)y=x csc(x)"
This equation is a linear equation of the form
"\\frac{dy}{dx} + P(x)y = Q(x)"
where
"P(x) = cot (x),\ud835\udc44(\ud835\udc65) = \ud835\udc65 csc(x)"
Integrating factor :
"IF(x) = e^ {\\int \ud835\udc43(\ud835\udc65)\ud835\udc51x }=e^ {\\int cot (x) \ud835\udc51x }=\\\\ =e^ {\\int \\frac{\ud835\udc51(sin\ud835\udc65)\n}{sin x} }= e^ {ln|sin\ud835\udc65| + \ud835\udc36}"
We are looking for a particular integrating factor, so we take C=0.
Then we get
"IF (x)= sin(\ud835\udc65)"
Multiply both sides of the equation by "IF (x)= sin(\ud835\udc65)"
"sin(\ud835\udc65) \\frac{dy}{dx} +(sin(\ud835\udc65) \u22c5cot(x))y=x csc(x)\u22c5 sin(\ud835\udc65)"
or
"sin(\ud835\udc65) \\frac{dy}{dx} + (cos(\ud835\udc65))\ud835\udc66 = \ud835\udc65"
i.e.
"\\frac{d}{dx}(\ud835\udc66 \u22c5 sin\ud835\udc65) = \ud835\udc65."
Integrate both sides of this equation we get the general solution
"\\int \\frac{d}{dx}(\ud835\udc66 \u22c5 sin\ud835\udc65)dx = \\int \ud835\udc65 dx \\Rightarrow \ud835\udc66 \u22c5 sin\ud835\udc65 = \\frac{\ud835\udc65^2}{2} +C" ,
where C - constant defined by the initial conditions.
Now we find C and solve the initial value problem.
Substitute the initial condition
"y(\\frac{\\pi}{2}) =1"
into the general solution:
"y(\\frac{\\pi}{2})\u22c5 sin(\\frac{\\pi}{2})= \\frac{(\\frac{\\pi}{2})^2}{2} +C \\Rightarrow \\\\1\u22c5 sin(\\frac{\\pi}{2})= \\frac{1}{2} (\\frac{\\pi}{2})^2+C,"
or
"1= \\frac{\\pi^2}{8}+C \\Rightarrow C= 1- \\frac{\\pi^2}{8}."
Then we obtain the solution for the initial value problem
"\ud835\udc66 \u22c5 sin\ud835\udc65 = \\frac{\ud835\udc65^2}{2} +1- \\frac{\\pi^2}{8}"
or
"\ud835\udc66 =( \\frac{\ud835\udc65^2}{2} +1- \\frac{\\pi^2}{8})csc(x)"
The solution for the initial value problem is
"\ud835\udc66 =( \\frac{\ud835\udc65^2}{2} +1- \\frac{\\pi^2}{8})csc(x)."
Comments
Leave a comment